2006
DOI: 10.1111/j.1463-5224.2006.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical effect of various agents on gelatinase activity in the tear film of normal dogs

Abstract: This study indicated that only EDTA was able to significantly reduce the gelatinase activity in a persistent manner in the tear film of normal canine eyes. Further studies will be required to evaluate the effect of EDTA under ulcerative conditions and to more accurately ascertain the potential in vivo effect of the other agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 31 publications
2
20
1
Order By: Relevance
“…In vivo only EDTA was able to appreciably inhibit gelatinase activity present on normal canine corneal surface (10). This activity is attributed to chelation of Zn, a metal required for MMP activity, by EDTA.…”
Section: Dose-dependent In Vitro Inhibition Of Rabbit Corneal Matrix mentioning
confidence: 92%
“…In vivo only EDTA was able to appreciably inhibit gelatinase activity present on normal canine corneal surface (10). This activity is attributed to chelation of Zn, a metal required for MMP activity, by EDTA.…”
Section: Dose-dependent In Vitro Inhibition Of Rabbit Corneal Matrix mentioning
confidence: 92%
“…Researches with tear proteins have always been performed in humans and animals (Ollivier et al 2004, Couture et al 2006), since they provide important information about the course and classification of some diseases and help to find diagnostic and therapeutic targets (Ananthi et al 2008). The Bradford method is suggested as a sensitive method of tear protein quantification (Sitaramamma et al 1998, Ham et al 2007, Ananthi et al 2008), as we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Lowry (Li et al 2010) and Bradford (Sitaramamma et al 1998, Ananthi et al 2008, Li et al 2010) methods were used to quantify proteins from tear samples (Ananthi et al 2008, Lu et al 2010. For proteomic analysis, tear samples can be obtained from microcapillary tubes (Gachon et al 1982, Jones et al 1997, Couture et al 2006, Grus et al 2007, Green-Church et al 2008 or from Schirmer tear test strips (Grus et al 2007, Li et al 2008, Roberts & Erickson 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs, a family of zinc‐ and calcium‐dependent proteinases, are secreted in an inactive state, as pro‐enzymes. Low levels of MMP‐2 and ‐9 (both gelatinases) are detectable in tears collected from healthy horses 14,15 and dogs 16 . The removal of nictitating membranes creates a surgically induced wound that has the potential to involve the expression of MMP‐2 and ‐9 akin to that reported in healing skin wounds 17–19 .…”
Section: Introductionmentioning
confidence: 99%